Culture Shock Dalam Interaksi Komunikasi Antarbudaya Suku Jawa dan Suku Batak di Kota Medan - Syafrida Syafrida; Anang Anas Azhar (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The research written is a research that raises the title of intercultural communication interaction between Javanese and Batak tribes in Medan City. This study has the aim of knowing the communication that exists between the Javanese and the Batak tribes in the city of Medan. The stages of intercultural communication, which will occur to the Javanese in the city of Medan and contain efforts to overcome the culture shock that will occur. The method that will be used in writing this research is qualitative by reading the literature on previous research that discusses culture shock. The results of this study will show that the Javanese will experience a moderate culture shock and have no significant effect on intercultural communication. This is because the Javanese quickly adapt and adjust to the interaction patterns that exist in the city of Medan. Based on previous research literature, he claimed to feel comfortable and safe living in the city of Medan compared to his own hometown, which made communication between one tribe and another run well and did not cause misunderstandings and harm others. Especially in this study, namely the Javanese tribe in the city of Medan. The influence of self-motivation and encouragement of interaction also affects the communication process that exists between the Javanese and the Batak tribes in the city of Medan. Friendships that exist in the campus environment, but not all Javanese want to make friends and interact with everyone, but Javanese people interact with all ethnic groups on campus, especially in the city of Medan. Keywords: Culture shock, Interaction, Javanese,